Strategy for Utilizing Massive Open Online Courses (MOOCs) to Enhance Critical Thinking Skills - Rahman, Fawait Syaiful (Universitas Nurul Jadid Probolinggo, Indonesia, 2024)
This study focuses on the development of learning strategies within Massive Open Online Courses (MOOCs) to enhance students' critical thinking skills. The main objective of this research is to explore and identify the effectiveness of selecting relevant materials, structuring modules, fostering interaction and active discussion, as well as utilizing technology and multimedia in improving critical thinking skills. This research employs a qualitative method with a case study approach, involving in-depth interviews, participant observation, and document analysis from courses attended by students on the MOOC platform. The findings indicate that the implemented strategies significantly enhance student engagement in learning and their ability to connect theory with practice. Students participating in courses with clearly structured modules, relevant materials, effective interaction, and technology usage demonstrate a noticeable improvement in critical thinking skills. The implications of this research suggest that a comprehensive and well-structured learning design can positively impact the development of students' analytical skills, which are crucial in the context of modern education.